Northern Shrimp (Pandalus borealis) on Flemish Cap in July 1996 - Río-Iglesias, José Luis del (1996)
A stratified random bottom-trawl surveys on Flemish Cap was carried out in July 1996 following the same method used since 1988 Results of shrimp population (Panda/us borealis) are presented in this paper and compared with those previously observed.